Table 1_Deep exploration of the TCR CDR3β repertoire specific for viral CD4 T-cell epitopes inside the circulating T-cell repertoire.docx - Gautier Lhomme (22687169) (2025)
Introduction This study provides an in-depth analysis of the diversity of the CD4 TCR CDR3β repertoire specific to influenza A (HA) and Epstein-Barr virus (EBNA) epitopes. Methods Epitope-specific CD4 T cells from 13 healthy donors were enriched using a short-term culture step, isolated based on activation markers, and sequenced for their TCR CDR3β region using high-throughput sequencing. The frequency of each clonotype was then identified within the complete circulating CD4 T-cell CDR3β repertoire. Results For both epitopes, the clonotype distribution was markedly skewed, with a small number of highly expanded clones comprising approximately 60% of the repertoire, alongside numerous low-frequency clonotypes. VJ gene usage and motif preferences differed between the two peptides, highlighting epitope-specific TCR selectivity. The response was predominantly composed of private T-cell clonotypes. The proportion of public clonotypes can increase among donors sharing HLA class II molecules and reveals in HLA-unrelated donors the level of TCR promiscuity. Discussion Overall, our data demonstrate that CD4 T-cell responses to these viral epitopes are polyclonal and highly personalized. The modest overlap of clonotypes between donors, coupled with a long tail of low-frequency clones, suggests that the full diversity of the epitope-specific T-cell repertoire is likely broader than previously estimated.